Proyecto de exportación de sabajón desde Paipa – Boyacá hacia Madrid - España (2023)
The current study focuses on the analysis of the Colombian liquor industry to venture into the international market. This interest arises from the significant growth experienced in various foreign markets, driven by the increasing demand for these liquors at various international fairs. Colombian liquors have stood out at these events, gaining solid acceptance among international consumers.